FEATURES OF UTERINE FIBROID VASCULARIZATION IN WOMEN WITH VITAMIN D DEFICIENCY - Irnazarova Dinara Khamidiloyevna (Scholar Express Journals, 2023)
Uterine fibroids are the most common pathology among women. We examined 200 women at the Multidisciplinary Clinic of the Tashkent Medical Academy. We studied the saturation of the body with vitamin D (25(OH)D) in patients with uterine fibroids (UF) and healthy women, moreover in order to identify ultrasound parameters in the studied women with UF, we performed color duplex scanning of the vessels of the internal iliac artery. In less than half of women with symptomatic fibroids, deficiency and severe deficiency of vitamin D prevails. In 1/3 of women with the symptomatic UF group, intense central blood flow was observed in the PP; in women with asymptomatic fibroids, with an avascular type of blood flow, in more than half of the women, the sizes of the uterus and nodes were minimal. The more pronounced the deficiency of this vitamin D, the more neoangiogenesis develops, leading to increased vascularization of the myomatous node, its growth, and the manifestation of clinical symptoms in these women.
Keywords: uterine fibroids; leiomyoma; symptomatic fibroids